Analysis of Shift Work Perception on Burnout Syndrome Levels in Inpatient Nurses at Bhayangkara Hospital, Kediri City - Happy Wahyuning Tyas; Amarin Yudhana (Universitas STRADA Indonesia, 2024)
Work shift is a work agenda that has been set by the workplace, which in its division can affect various things such as the occurrence of burnout syndrome. Burnout is fatigue caused by work. Workers who often experience burnout problems include nurses. With the existing workload, nurses have a high risk of developing burnout syndrome. The method used in this study uses a cross-sectional method with a sample size of 122 respondents. The SPSS test carried out was using the chi-square test. The results of this study indicate a significant influence between work shifts on the level of burnout syndrome in inpatient nurses at the Bhayangkara Hospital in Kediri City. With a significance value of 0.006 (P <0.05). Conclusion, Based on the results of this study, it can be concluded that if the work shift is effective, the level of burnout syndrome tends to be low, but if the work shift is not effective, the level of burnout syndrome will tend to be high.